Granulomatous Hepatitis Secondary to Histoplasma Infection after Treatment with Infliximab - L. Barrera; J. Álvarez; M. Tapias; V. Idrovo; R. López (Case Reports in Hepatology)
Classical presentation of Histoplasma infection includes fever and respiratory symptoms. Opportunistic microorganisms must be suspected on immunocompromised patients who develop bizarre symptoms. We present a case of a female patient with rheumatoid arthritis who received treatment with Infliximab during one and a half year; she developed granulomatous hepatitis secondary to Histoplasma infection. The patient was admitted with acute hepatitis and thrombocytopenic coagulopathy. A liver biopsy was performed revealing granulomatous hepatitis, microvesicular steatosis, isolated apoptotic cells, and parenchyma microabscesses. PAS and Gömöri stains revealed areas with mycotic microorganisms morphologically compatible with Histoplasma spp. and confirmed by culture.